Vegetation succession in deglaciated landscapes: implications for sediment and landscape stability. Issue 8 (23rd December 2014) - Klaar, Megan J.; Kidd, Chris; Malone, Edward; Bartlett, Rebecca; Pinay, Gilles; Chapin, F. Stuart; Milner, Alexander
Abstract Landscapes exposed by glacial retreat provide an ideal natural laboratory to study the processes involved in transforming a highly disturbed, glacially influenced landscape to a stable, diverse ecosystem which supports numerous species and communities. Large‐scale vegetation development and changes in sediment availability, used as a proxy for paraglacial adjustment following rapid deglaciation, were assessed using information from remote sensing. Delineation of broad successional vegetation cover types was undertaken using Landsat satellite imagery (covering a 22 year period) to document the rate and trajectory of terrestrial vegetation development. Use of a space‐for‐time substitution in Glacier Bay National Park, Alaska, allowed 'back‐calculation' of the age and stage of development of six catchments over 206 years. The high accuracy (89.2%) of the remotely sensed information used in monitoring successional change allowed detection of a high rate of change in vegetation classes in early successional stages (bare sediment and alder). In contrast, later successional stages (spruce and spruce–hemlock dominated forest) had high vegetation class retention, and low turnover. Modelled rates of vegetation change generally confirmed the estimated rates of successional turnover previously reported. These data, when combined with the known influence of terrestrial succession on soil development and sediment availability, suggest how physical and biological processes interact over time to influence paraglacial adjustment following deglaciation. This study highlights the application of remote sensing of successional chronosequence landscapes to assess the temporal dynamics of paraglacial adjustment following rapid deglaciation and shows the importance of incorporating bio‐physical interactions within landscape evolution models. © 2014 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd.